Investigation into Consumer Response to Sales Promotional Activities: The Case of Unilever Ghana Limited - Martin Owusu Ansah; Kofi Poku (International Review of Management and Marketing, 2013)
The promotional activities have become more sophisticated and an increasing number of companies are using them to ensure their survival in today’s competitive market. Essentially, the study analyzed the nature of sales promotional activities of Unilever Ghana Limited; determined factors that influence the consumption of Unilever products in Kumasi and finally examined the relationship between sales promotions and the consumption of Unilever products. Primary and secondary data sources were used to select 220 consumers of Unilever in Kumasi and an in-depth interview with the Managers of the companies in Kumasi. Convenient sampling technique was employed in the study. Cross tabulation was done on the demographics whilst a regression model was used to establish the relationship between sales promotions and consumption of products. The findings revealed that Personalities in promotions, Prices in promotions, Messages in promotions and Promotional tools have strong influence on consumption but the Medium in promotion did not have influence on consumption during promotions. It was therefore recommended for celebrities to be used in the company’s promotions.